Phytoremediation of heavy metals and desalination of brackish water with ipomoea aquatica using aquaponics system - Lee, Pei Qi (2016)
This study presents the phytoremediation and desalination of heavy metals in brackish water with Ipomoea aquatica in an aquaponics systems. The study of phytoremediation by Ipomoea aquatica in saline condition had not been study extensively. Ipomoea aquatica was separated into roots and shoots and the scales of tilapia fish was harvested at Day-0 and Day-30 from two aquaponics tanks. The purpose for this research was to investigate the phytoremediation and desalination capability of Ipomoea aquatic. Synthetic saline water and field water collected from Kuantan Estuary were sent for ICP-MS analysis at Day-0 and Day-30 to determine the concentration of 22 types of metal elements contained. The field water sampled from Kuantan Estuary showed a decrease in Na, Mg, K and Ca from Day-0 to Day-30. This indicated that Ipomoea aquatica was able to uptake major constituents that contributes to the salinity and has potential in desalination. Na was decreased to 4692.0 ppm from 14070.0 ppm, showing a percentage of 66.65%. Mg had reduced as much of 77.47%, from 1630.0 ppm to 367.2 ppm. K had a reduction rate of 64%, depleting from 446.0 ppm to 159.0 ppm while Ca had a reduction rate of 68.54% when the initial concentration of 486.7 ppm had plunged to 153.1 ppm at Day-30. Cr decreased 33.33%, from 84.0 ppb to 56.0 ppb. There was a total of 12 samples and the samples were subjected to wet digestion. The samples were then analyzed for its Mg content. The samples generally showed an increase in Mg concentration from Day-0 to Day-30. The parameters of water from both tanks including pH, DO, EC, TDS, salinity and temperature were taken as background data throughout the commence of experiment. Conductivity, total dissolved solids and salinity reduced from Day-0 till Day-35 in both tanks as the metal ions were being absorbed by plant biomass and fish scales. In conclusion, the built aquaponics systems were able to phytoremediate heavy metal-contaminated field water by translocating the pollutants within the tissues of Ipomoea aquatica and the scales of tilapia.